Does Islamic Screening Affect Unit Trust Fund Performance in Malaysia - Abdul Rashid, Azillia (2005)
Over the past 20 years, the pace of the Islamic financial market’s development has gained considerable interest as it is seen as an alternative model of financial intermediation in many Muslim as well as several non-Muslim countries. In line with this development, Malaysia has developed a vision of becoming an international Islamic capital market for the Asian region. In order to attract foreign investors into the country, it must prove that it can be a viable alternative to the conventional financial system. This extends to the unit trust industry as investors can now invest in either Islamic or conventional funds. Therefore, the performance of Islamic versus conventional funds has become a topic of interest. This study aims to analyse the financial performance of 84 Islamic and conventional trust funds over a 42 month period from January 2002 to June 2005. Based on traditional modern portfolio theory (MPT), as Islamic funds are faced with additional constraints compared to conventional funds, its performance is believed to lag behind those of conventional funds. The performance measures used in this study include the non riskadjusted average monthly returns as well as the risk-adjusted Adjusted Sharpe Index and the CAPM-based Jensen’s alpha measure. The results of the study indicate that Islamic funds do under-perform conventional funds, but the difference is only statistically significant for the Adjusted Sharpe Index. Among the reasons suggested for the difference in findings may be due to the method of calculating each measure and that there is more unsystematic risk present in the conventional funds to show a significant outperformance for conventional funds. Therefore, this is in line with the MPT where higher returns may be achieved as a result of assuming higher risks.